A study on factor which affect employee’s retention at Naza Kia Malaysia Sdn. Bhd. / Nursazlina Akmal Muhamad Ali - Muhamad Ali, Nursazlina Akmal (Faculty of Business and Management, 2011)
Employee retention is an ability of the organization to retain their employees. Many consider employee retention as relating to the efforts by which employers attempt to retain employees in the workforce. Retention is become the strategies in the organization in order to make it has a competitive advantage. In a business setting, one of the employer goals is to decrease the turnover rate because it can reduce the recruiting expenses, orientation for new employee, training cost and decrease in productivity. The most important factor that the employer need to look seriously in retaining employee are not to lose the talented and knowledgeable employee because it is a big lost if the company is losing them. This is because key employee make the company growth, successful and able to achieve the organization goals by increase the profits of company. Moreover, they are the backbone of the company which is lead to the direction and future of the organization. The labour market continues to tighten and there are less available skilled, loyal and motivated employees (Memmott, 2002). High motivation can lead employee to stay in the organization. This is because motivation is the force that makes us do things. To motivate the employee, employer require to provide compensation and benefits that truly meet employee needs. The logical reason people go to work because they need money in order to survive and complete their basic needs. Then, their needs will change to physical needs, safety needs and social needs, so the employer obliges getting alert with this changing to satisfied employees. When individual needs being satisfied so they will have support to complete the task or work. Research has shown that there may be many environmental features that can be created and maintained to give employees job satisfaction. Pay and benefits, communication, motivation, justice and leisure time all seem to play a part as to whether employees are satisfied with their jobs (Paul L. Gerhardt, Jr.). Only the employee that satisfied will stay in the organization. When employee chose to stay, the turnover rate is low. In order to do so, employer should take an action to make sure that the employee is satisfied with their job by giving the opportunity to learn, develop and involving in the decision making. Nowadays, the challenge of organization to retain their employee is high because needs are different in time to time and changing fast to cope with the environment. In order the organization want to stay as competitive advantage, they must understand what are the needs has to fulfil and been offer to them. The current study on employee’s retention helps to know as much about the most influence factors which element the employees want to stay and retain in the company. This will help the management to create suitable package of benefits to motivate the employees to stay. Hence, it can retain and attract more workers to work in the company. In this study, it includes four factors the most affect the employee to stay in company which is compensation, learning opportunity and work/life balance.